Alla ricerca del contesto del volgarizzamento della Historia Normannorum di Amato di Montecassino: il manoscritto francese 688 della Bibliothèque nationale de France - Kujawiński, Jakub (Istituto Storico Italiano per il Medioevo, Roma, 2010)
Looking for the context of the vernacular translation of Amatus of Montecassino’s Historia Normannorum (the French MS 688 of the National Library of France). The considered manuscript (Southern Italy, mid-14th cent.) has been known mainly for its being a unique testimony of the Historia Normannorum, an important historiographical narration on the Norman conquest of Southern Italy, written at the end of the 11th century. The author emphasizes that the manuscript and miscellany themselves (containing translations of Isidore of Seville’s Chronica, Paul the Deacon’s Historia romana and Historia Langobardorum, and of the so-called Historia Sicula) are worth studying and that only such an integral approach may enable the evaluation of French translation as the testimony of a lost Latin original. The following questions are discussed: paleographical and codicological features of the manuscript, its illuminations, the time and milieu of production of both the manuscript and the translations, the models for the miscellany, the relationship between single translations and the manuscript tradition of respective Latin compositions and the place occupied by the considered manuscript in the transmission of the miscellany.
Keywords: Amatus of Montecassino; Paris, Bibliothèque nationale de France, fr. 688; Medieval Italy; Medieval Historiography; Angevins (dynasty); Medieval French translations; Manuscript Studies; Normans (people)